Analisis Kemampuan Literasi Matematis Peserta Didik Di Kelas XI IPA 1 MAN 1 Padang Berdasarkan Kemampuan Matematika - Khairunnisa, Khairunnisa; Sepriyanti, Nana (Math Educa Journal, 2019)
This is a descriptive research with a qualitative approach. The research subjects are 3 students of class XI.1 Natural Science in Public Islamic Senior High School (MAN) 1 Padang. They are different in terms of their mathematics ability; low, medium, and high. The data are collected by documentation, test method, and deep interview method. The data analyzed were the data of mathematical literacy skills test result and interview result. Mathematical literacy skills analysis by using PISA indicator revealed that student with low mathematics ability (S1) is at level 2 of mathematical literacy skills, Student with medium mathematics ability (S2) is at level 3 of mathematical literacy skills. This is due to the student ability to fulfill all indicators of questions at level 1, 2, and 3. Next, the student with a high mathematics ability (S3) is at level 5 of mathematical literacy skills since the student is able to fulfill the literacy indicator at level 1, 2, 3, 4, and 5. However, at level 6, S3 find it difficult to analyze the questions.